Rations containing sorghum, corn, or wheat with 0 or 4% added fat for weaned pigs - G L Allee (Kansas Agricultural Experiment Station Research Reports, 1977)
One hundred eight crossbred, weaned pigs averaging 10.0ks (22.1 lbs.) were used to compare rations containing sorghum, corn, or wheat with 0 or 4% added fat (tallow) on performance of young pigs. There were no significant differences in average daily gain or feed efficiency among pigs fed sorghum, corn, or wheat with no added fat; and adding 4 % fat to the rations did not affect gain but did result in a slight improvement in feed/gain.; Swine Day, Manhattan, KS, November 10, 1977
Keywords: Swine day; 1977; Kansas Agricultural Experiment Station contribution; no. 78-101-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 312; Swine; Sorghum; Corn; Wheat; Fat; Weanling pigs